237 Jejunum lymph node transcriptome reveals the importance of genes of phagosome and T cell receptor signalling pathways in Mycobacterium avium ssp. paratuberculosis infection. (7th December 2018) - Do, D; Dudemaine, P; Bissonnette, N; Ibeagha-Awemu, E
Abstract: Mycobacterium avium ssp. paratuberculosis (MAP) is the causative agent of Johne's disease (JD). MAP infects ruminants and resides in the intestinal submucosa, macrophages/dendritic cells causing progressive weight loss and decreased productivity. The molecular mechanisms by which MAP subverts host immune system causing extensive formation of granulomas and tissue damage are poorly understood.HRSP12 (p=4.43E-05), PCDHGA5 (p=4.43E-05), NFYA (p=1.48E-04) and HLA-DOB (p=1.48E-04) might have proles in MAP infection. For example, HLA-DOB gene encodes a protein in the MHC Class II with critical roles in the initiation of antigen-specific immune responses. Phagolysosome membrane (p.FDR=3e-08) and neutrophil degranulation (p.FDR=6.83–07) were the most enriched cellular components and biological processes GO terms, respectively, thus supporting the roles of genes in these immune related processes in the regulation of JD. Pathways enrichment identified phagosome, metabolic, tuberculosis, carbon metabolism, Vibrio cholerae infection pathways, and pathways essential for T-cell functions (RAC1 signaling, TCR signaling in naive CD4+ T cells and CD8+ T cells, Thromboxane A2 receptor and IL8 signalling pathways) as important for MAP infection.